#### Answer

$128i$

#### Work Step by Step

$(-2i)^7 = (-2)^7 \cdot i^7 = -128 \cdot i^4 \cdot i^3 = -128 \cdot 1 \cdot -i = 128i$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$128i$

$(-2i)^7 = (-2)^7 \cdot i^7 = -128 \cdot i^4 \cdot i^3 = -128 \cdot 1 \cdot -i = 128i$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.